ChemInform Abstract: Halocyclization of Unsaturated Guanidines Mediated by Koser′s Reagent and Lithium Halides. Issue 11 (February 2016) - Daniel, Marion; Blanchard, Florent; Nocquet‐Thibault, Sophie; Cariou, Kevin; Dodd, Robert H.
Abstract: Both the bromo‐ and the chlorocyclization of unsaturated guanidines are achieved by Kosers reagent‐mediated umpolung of the lithium halide.